2004
DOI: 10.1111/j.1523-1755.2004.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired response of the denervated kidney to endothelin receptor blockade in normotensive and spontaneously hypertensive rats

Abstract: An interaction between ET and renal nerves is involved in the control of renal function. Moreover, renal nerves participate in the regulation of ET-1 production within the kidney. Finally, decreased synthesis of ET-1 in the renal papilla of spontaneously hypertensive rats may contribute to development and/or maintenance of hypertension due to modulation of renal excretory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
(41 reference statements)
3
9
1
Order By: Relevance
“…The effects of bosentan are in agreement with our previous findings in SHR showing that bilateral renal denervation modulated the response to the ET A receptor antagonist BQ-123 [13] . From these results we suggest that an inadequate ET-1 synthesis and a reduced ET receptor number in the renal papilla of SHR in the presence of increased ERSNA [7] contributes to enhanced renal sodium retention in young [35] and adult [36] SHR and may thereby play a crucial role in the pathogenesis of hypertension in this genetic model.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The effects of bosentan are in agreement with our previous findings in SHR showing that bilateral renal denervation modulated the response to the ET A receptor antagonist BQ-123 [13] . From these results we suggest that an inadequate ET-1 synthesis and a reduced ET receptor number in the renal papilla of SHR in the presence of increased ERSNA [7] contributes to enhanced renal sodium retention in young [35] and adult [36] SHR and may thereby play a crucial role in the pathogenesis of hypertension in this genetic model.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, confirming our previous findings [13] and those of others [24] , we found that ET-1 content and prepro-ET-1 mRNA in the renal papilla are significantly lower in SHR than in WKY rats. These findings suggest an intrinsic defect in the renal ET system in SHR and are further supported by the observations that urinary ET excretion is lower in SHR compared to WKY rats [24] and that recipients of an SHR kidney exhibit a lower rate of urinary ET excretion than recipients of a kidney from WKY rats [5] .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Patients with hypertension, in particular those with salt-sensitive hypertension, were found to excrete less ET-1 in their urine than normotensive subjects, indicating reduced renal ET-1 production in the hypertensive subjects (119). Reduced production of ET-1 in the renal medulla has also been found in some animal models of hypertension (120,121). Underlining the importance of the intrarenal endothelin system in the control of blood pressure and sodium and water homeostasis, mice with collecting duct-specific knockout of the ET-1 gene are hypertensive on a normal salt diet, and this hypertension is exacerbated by exposure to a high salt diet (43).…”
Section: Essential Hypertensionmentioning
confidence: 99%